Clinical audit of rectal cancer patient referrals for Papillon contact brachytherapy. Issue 4 (4th December 2020) - Baker, A.; Buckley, L.; Misra, V.; Bridge, P.
Abstract: Background and purpose: Papillon treatment is a form of contact X-ray brachytherapy (CXB) which is used as an alternative to surgery for rectal cancer. This study aimed to audit patients who were referred for and treated with CXB over a 6-year period against guidelines derived from a critical review of the evidence base. Materials and methods: Patient demographics, tumour characteristics and outcome data were gathered for 31 patients referred for CXB. A critical review of the evidence identified consensus referral criteria and outcome data against which to audit patients. Results: Referral criteria were derived from six published studies. These applied to patients unfit for surgery or stoma-averse. All referred patients had a visible tumour or scar with a tumour size under 3 cm and sited less than 12 cm from the anal verge. Nodal status varied from N0 to N2, but there was no metastatic disease present. The audited cohort demonstrated demographic equivalence, while the initial clinical complete response and recurrence rates were also comparable. Conclusion: This audit confirmed the validity of referral and treatment protocols and should guide future referrals until evidence from ongoing studies becomes available. These findings should contribute to the development of robust national guidelines.